Self-Control: Protecting Students' Mental Health from Fear of Missing Out (FOMO) - Najib, Ariz; Rahmawati, Regina Putri (Hasanuddin Journal of Sociology (HJS), 2024)
Social media facilitates the reception and delivery of everyday information, increasing access to information for users, but it also plays a role in the emergence of Fear of Missing Out (FoMO). FoMO is the fear of missing out on valuable experiences that others have, driving the desire to stay connected to other people's activities. This research uses a qualitative approach with a case study method, conducted by interviewing 4 social studies education students from the class of 2021 with the criteria that several friends indicated FoMO with a purposive sampling technique. The results show that all respondents spend more than 1.5 hours per day on social media and have felt the impact of FoMO, although it has not reached the level of severe mental health disorders. From the interview results, respondents agreed that self-control plays an important role in minimizing FoMO. Social media, with its intensity of use and frequent viewing of others' posts, is believed to be a trigger for FoMO that can negatively impact mental health. Focusing too much on these platforms can lead to anxiety, lack of confidence, and dissatisfaction with one's own life, even triggering mental health issues such as anxiety and depression. In overcoming FoMO, self-control is recognized as the key. Timing social media use, limiting exposure to FoMO-inducing content, and focusing on personal life are considered effective strategies to reduce the negative impact of FoMO on mental health. Thus, increasing self-control can be an important step in maintaining emotional and psychological balance in this digital age.